تأثير وسائل التواصل الاجتماعي على الوعي السياسي: السودان دراسة حالة 2020-2025م - عبدالله, محمد خالد محمد (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 1 (2023), 2026)
هدفت هذه الدراسة إلى تحليل تأثير وسائل التواصل الاجتماعي على مستوى الوعي السياسي في الدول النامية، مع تطبيق الدراسة ميدانياً في السودان خلال الفترة من 2020 إلى 2025. وتأتي أهمية هذه الدراسة في ظل التحولات السياسية والاجتماعية التي شهدها السودان خلال هذه الفترة، حيث برزت وسائل التواصل الاجتماعي كأحد أهم الوسائل المؤثرة في تشكيل الرأي العام ونشر المعلومات السياسية بين فئات المجتمع، خاصة الشباب. اعتمدت الدراسة على المنهج الوصفي التحليلي، كما استخدمت أدوات جمع البيانات المتمثلة في الاستبيان والمقابلات، والتي طُبقت على عينة من مستخدمي وسائل التواصل الاجتماعي في السودان. وقد هدفت هذه الأدوات إلى قياس مدى استخدام هذه الوسائل وتأثيرها في مستوى المعرفة السياسية والمشاركة في النقاشات العامة والقضايا الوطنية. وأظهرت نتائج الدراسة أن وسائل التواصل الاجتماعي تمثل مصدراً رئيسياً للمعلومات السياسية لدى العديد من المستخدمين، حيث ساهمت في رفع مستوى الوعي بالقضايا السياسية وتعزيز المشاركة في النقاشات العامة. كما أسهمت في توسيع فرص التعبير عن الآراء السياسية والمشاركة في الحملات والأنشطة السياسية عبر الفضاء الرقمي ومع ذلك، كشفت الدراسة أيضاً عن بعض التحديات، مثل انتشار المعلومات غير الدقيقة، والاستقطاب السياسي، وتأثير المحتوى غير الموثوق على تشكيل الرأي العام. توصي الدراسة بضرورة تعزيز الوعي الإعلامي والرقمي لدى المستخدمين في السودان، وتشجيع المؤسسات التعليمية والإعلامية على نشر ثقافة التحقق من المعلومات، إضافة إلى تطوير سياسات إعلامية وتشريعية تدعم الاستخدام المسؤول لوسائل التواصل الاجتماعي بما يسهم في تعزيز الوعي السياسي وترسيخ قيم المشاركة الديمقراطية في المجتمع.       This study aimed to examine the impact of social media on political awareness in developing countries, with a field study conducted in Sudan during the period from 2020 to 2025. The significance of this research arises from the political and social transformations experienced in Sudan during this period, where social media platforms emerged as influential tools in shaping public opinion and disseminating political information among different segments of society, particularly youth.The study adopted a descriptive analytical approach and employed data collection tools including questionnaires and interviews conducted with a sample of social media users in Sudan. These tools were designed to measure the extent of social media use and its influence on political knowledge and engagement in public and national discussions.The results indicated that social media has become a primary source of political information for many users in Sudan, contributing to increased awareness of political issues and encouraging participation in public discussions. These platforms also provided wider opportunities for political expression and digital activism. However, the study also identified several challenges associated with social media use, including the spread of misinformation, political polarization, and the influence of unreliable content on public opinion formation.The study recommends enhancing digital and media literacy among social media users in Sudan, encouraging educational and media institutions to promote fact-checking practices, and developing policies that support the responsible use of social media in order to strengthen political awareness and democratic participation in Sudanese society.